2020
DOI: 10.1016/j.heliyon.2020.e05116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of local SARS-CoV-2 isolates and pathogenicity in IFNAR−/- mice

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) recently a global pandemic with unprecedented public health, economic and social impact. The development of effective mitigation strategies, therapeutics and vaccines relies on detailed genomic and biological characterization of the regional viruses. This study was carried out to isolate SARS-CoV-2 viruses circulating in Anatolia, and to investigate virus propagation in frequently-used cells and experimental animals. We obtained two SARS-CoV-2 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 36 publications
(42 reference statements)
0
38
0
Order By: Relevance
“…IFNAR-deficient mice have been suggested as a potential animal model for SARS-CoV-2 experiments (Hanifehnezhad et al, 2020). In this study, we attempted to establish a mouse model of coronavirus-related severe acute respiratory distress syndrome (ARDS) by MHV.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…IFNAR-deficient mice have been suggested as a potential animal model for SARS-CoV-2 experiments (Hanifehnezhad et al, 2020). In this study, we attempted to establish a mouse model of coronavirus-related severe acute respiratory distress syndrome (ARDS) by MHV.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…In the study, the most frequently-detected variations, namely the A23403G, C14408T and GGG28881AAC mutations resulting in amino acid substitutions in the corresponding virus proteins, were reported in previous analyses from Turkey [23][24][25]. However, they seem to be positively-selected in the local virus population pool, as their abundance seem to be elevated.…”
Section: Discussionmentioning
confidence: 76%
“…Research using animal models to investigate the COVID-19 infection has important implications for antiviral and vaccine studies. For instance, transgenic type I interferon knockout mice (IFNAR −/− ) have been suggested as an effective animal model for these studies (Hanifehnezhad et al, 2020). The results obtained in this study showed that cats cannot serve as a suitable animal model for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 85%
“…The virus was collected from clari ed cell culture supernatants and aliquoted and frozen at − 80°C until use. The SARS-CoV-2-Ank1 strain used to infect the cells was provided by the Biosafety Level 3 Plus (BSL3+) facility of the Virology Department, Faculty of Veterinary Medicine at Ankara University (Hanifehnezhad et al, 2020).…”
Section: Virus and Cell Culturementioning
confidence: 99%